Modeling neural differentiation on micropatterned substrates coated with neural matrix components - García-Parra, Patricia; Cavaliere, Fabio; Maroto, Marcos; Bilbao, Leire; Obieta, Isabel; López de Munain, Adolfo; Álava, José Iñaki; Izeta, Ander (Frontiers in Cellular Neuroscience, 2012)
Topographical and biochemical characteristics of the substrate are critical for neuronal differentiation including axonal outgrowth and regeneration of neural circuits in vivo. Contact stimuli and signaling molecules allow neurons to develop and stabilize synaptic contacts. Here we present the development, characterization and functional validation of a new polymeric support able to induce neuronal differentiation in both PC12 cell line and adult primary skin-derived precursor cells in vitro. By combining a photolithographic technique with use of neural extracellular matrix as a substrate, a biocompatible and efficient microenvironment for neuronal differentiation was developed.